Angular Correlation between Photoelectrons and Auger Electrons from K-Shell Ionization of Neon - Landers, A. L.; Robicheaux, F.; Jahnke, T.; Schöffler, M.; Osipov, T.; Titze, J.; Lee, S. Y.; Adaniya, H.; Hertlein, M.; Ranitovic, P.; Bocharova, I.; Akoury, D.; et al. (My University, 2009)
We have used cold target recoil ion momentum spectroscopy to study the continuum correlation between the photoelectron of core-photoionized neon and the subsequent Auger electron. We observe a strong angular correlation between the two electrons. Classical trajectory Monte Carlo calculations agree quite well with the photoelectron energy distribution that is shifted due to the potential change associated with Auger decay. However, a striking discrepancy results in the distribution of the relative angle between Auger and photoelectron. The classical model predicts a shift in photoelectron flux away from the Auger emission direction, and the data strikingly reveal that the flux is lost rather than diverted, indicating that the two-step interpretation of photoionization followed by Auger emission is insufficient to fully describe the core-photoionization process.